Effect of γ-PGA on the formation of collagen fibrils in vitro. (3rd July 2016) - Ding, Cuicui; Zheng, Zhigong; Liu, Xinzhong; Li, Hengda; Zhang, Min
ABSTRACT: The effect of γ-poly(glutamic acid) (γ-PGA) on the self-assembly of collagen was studied. Under physiological conditions, the kinetic curves for fibril formation showed that the turbidity of collagen/γ-PGA blends at 313 nm was increased with the addition of γ-PGA. Furthermore, it was shown using both field-emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) that fibrils with a larger diameter were obtained following the addition of γ-PGA, probably due to the electrostatic and hydrogen bond interactions between collagen and γ-PGA, which promoted the lateral association of collagen molecules. In addition, both the thermal stability and viscoelastic properties of the hybrid hydrogels, which were evaluated by differential scanning calorimetry and rheological measurements, respectively, were improved by the addition of γ-PGA.